Local Wisdom in Herbal Medicine Processing: The Role of Health Practitioners in Maintaining Tradition and Innovation - Bayani, Faizul; Hulyadi, Hulyadi; Yuliana, Depi; Listantia, Nora; Hamdani, Ade Sukma (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study explores the role of local wisdom in traditional herbal medicine processing among the Sasak community in Lombok, Indonesia. The focus is on the extraction techniques used by traditional healers (belian), especially their selection of specific woods for the heating process to preserve the stability of bioactive compounds. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation involving experienced traditional practitioners. The findings show that belian possess inherited empirical knowledge that integrates technical, ecological, and spiritual considerations. This includes selecting herbal plants based on environmental quality, using sustainable harvesting methods, and applying low-heat boiling techniques to prevent degradation of sensitive compounds such as flavonoids and alkaloids. Additionally, spiritual rituals and intuitive practices accompany the preparation process, reflecting a holistic healing philosophy. The study reveals that these traditional methods align with modern principles of sustainable and effective herbal extraction. The integration of traditional knowledge with scientific understanding presents an opportunity to develop culturally rooted, low-cost, and environmentally friendly healthcare solutions. The preservation and documentation of this local wisdom are essential for future generations and the advancement of ethnopharmacological science.